Bulevirtide improves health-related quality of life measured by EQ-5D VAS in patients with chronic hepatitis delta: An exploratory analysis of a Phase 3 trial at 48 weeks. (March 2023) - Buti, M.; Wedemeyer, H.; Aleman, S.; Chulanov, V.; Morozov, V.; Sagalova, O.; Stepanova, T.; Gish, R. G; Lloyd, A.; Kaushik, A. M; Suri, V.; Manuilov, D.; et al.
Abstract : Introduction: Chronic hepatitis delta (CHD) is the most severe form of viral hepatitis and is associated with rapid progression to cirrhosis, decompensation, hepatocellular carcinoma, and end-stage liver disease. Aim: We report an exploratory analysis of EuroQol 5D visual analog scale (EQ-5D VAS) scores in patients with CHD after 48 weeks of treatment with bulevirtide (BLV) in an ongoing Phase 3 trial. Methods and Results: MYR301 (NCT03852719) is a randomized, open-label, parallel-group, multicenter trial that assigned 150 patients with CHD (1:1:1) to BLV 2 mg (n=49), BLV 10 mg (n=50), or control (n=51) for up to 3 years. Control patients received no BLV treatment until week 48 (W48). The EQ-5D VAS is a self-completed rating of patients' quality of life (QOL) with a range of 0–100 (100=best health state). The QOL analysis was based on EQ-5D VAS scores at baseline and W48. Baseline characteristics were well balanced across groups. At W48, patients with CHD treated with BLV 2 mg reported statistically significant improvement in QOL (by EQ-5D VAS) and significantly better EQ-5D VAS change from baseline scores when compared with control patients (Table). Changes from BL with BLV 10 mg were not statistically significant at W48 A cirrhosis-specific subgroup analysis indicated similar improvement trends among patients with or without cirrhosis; however, statistical significance was not reached. Conclusion: Patients with CHD treated with BLV 2 mg experienced improvements in QOL measured by the EQ-5D VAS at W48. EQ-5D VAS scores significantly improved in the BLV 2 mg group compared with baseline and compared with controls at W48 but did not in the BLV 10 mg group. Further investigation is needed to understand the impact of BLV 10 mg and the long-term effects of BLV treatment.